Total Knee Arthroplasty in Ochronosis Arthropathy: A Case Report and Systematic Review - Wu Chean Lee; Tong Leng Tan; Ying Ho Chan (Case Reports in Orthopedics)
Introduction. Ochronosis arthropathy (OcA) is a rare condition which may be treated with total knee arthroplasty (TKA) at the end stage. The condition is often discovered only intraoperatively and the ideal choice of TKA is unknown. Case Presentation. A 54-year-old male with worsening chronic bilateral mechanical knee pain had failed conservative therapy. Posterior stabilised (PS), cemented TKA and patella resurfacing was performed. Intraoperatively, collagenous structures such as the menisci and cartilage were noted to be black. Histological examination showed deposition of large amorphous brown material suggestive of ochronosis. He recovered well and underwent TKA of the contralateral knee the following year. At 2 years postindex TKA, his outcome scores improved and he was satisfied. Discussion and Conclusion. With increasing TKA performed worldwide, a surgeon may eventually be surprised by the above findings once in their lifetime. However, OcA may be considered a likely diagnosis and it is safe to proceed with TKA. There is no particular TKA design that proved to be superior in our systematic review of 19 publications regarding TKA as all reported good outcomes. However, as the pathogenesis of OcA appears to be inflammatory in nature, we suggest using cemented PS TKA with resurfacing of the patella.